2018
DOI: 10.3390/su10082868
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Driving Risk of Near-Crash Events Using a Mixed-Ordered Logit Model

Abstract: Abstract:With the considerable increase in ownership of motor vehicles, traffic crashes have become a challenge. This paper presents a study of naturalistic driving conducted to collect driving data. The experiments were performed on different road types in the city of Wuhan in China. The collected driving data were used to develop a near-crash database, which covers driving behavior, near-crash factors, driving environment, time, demographics, and experience. A new definition of near-crash events is also prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 30 publications
(41 reference statements)
3
32
0
Order By: Relevance
“…is the unobserved disturbance term. e traditional ordered logit model arises by assuming the disturbance term to be identically and independently standard logistic distributed [34]. In the framework of traditional ordered logit model, the observed driver injury severity can be mapped from through the threshold , where, is the threshold for splitting the observed injury severity to be estimated and 0 is normalized to 0. e probability of observed injury severity outcomes for driver are described as, where, (⋅) is the cumulative distribution function for the .…”
Section: Crash Injury Severitymentioning
confidence: 99%
“…is the unobserved disturbance term. e traditional ordered logit model arises by assuming the disturbance term to be identically and independently standard logistic distributed [34]. In the framework of traditional ordered logit model, the observed driver injury severity can be mapped from through the threshold , where, is the threshold for splitting the observed injury severity to be estimated and 0 is normalized to 0. e probability of observed injury severity outcomes for driver are described as, where, (⋅) is the cumulative distribution function for the .…”
Section: Crash Injury Severitymentioning
confidence: 99%
“…Wang et al [22] adopted the classification and regression tree model (CART) to study the association among driving risk, driver/vehicle characteristics, and road environment. Naji et al [23] used the mixed-ordered logit model for evaluating driving risk based on near-crashes. The model was used to examine the contributing factors associated with the driving risk of near-crash events.…”
Section: Related Workmentioning
confidence: 99%
“…Like [19] and [22], a naturalist study was conducted to collect data; however, self-reported data of historical factors was gathered using a questionnaire. Furthermore, unlike [23,24], hierarchical clustering was used to classify drivers according to their driving risk level. Although the near-crash concept is used as a surrogate measure to evaluate the safety impact of driving behavior in this study, as in [22,24], the parameters used for near-crashes are different, namely braking pressure, time headway, and deceleration.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the other 80% of crashes are ignored in the TSIP or the identification of hazardous locations, even though the unreported minor crashes could indicate a high risk for injuries or fatal crashes in the 2 of 16 near future [6]. When considering the safety pyramid by Hydén [7], the unreported minor crashes, as well as latent risk factors such as near misses and traffic conflicts, might cause injuries or a major crash [8].…”
Section: Introductionmentioning
confidence: 99%